2019
DOI: 10.1039/c8en01198b
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the reactive surface area of ferrihydrite: time, pH, and temperature dependency of growth by Ostwald ripening

Abstract: Surface area is a crucial property of ferrihydrite that has been assessed by probing it with PO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 77 publications
(121 reference statements)
0
67
1
Order By: Relevance
“…Calcium interacts with the OM COOH sites that partially screen the interactions between Fe and OM [8]. As a consequence, the size of the Fh-like Nps increases, which should involve a decrease in their SSA and q max [40,[44][45][46]. Surprisingly, our results did not confirm these expectations: q max and the SSA increased concomitantly with the increasing size of Fh-like Nps (Figure 6).…”
Section: Discussioncontrasting
confidence: 71%
“…Calcium interacts with the OM COOH sites that partially screen the interactions between Fe and OM [8]. As a consequence, the size of the Fh-like Nps increases, which should involve a decrease in their SSA and q max [40,[44][45][46]. Surprisingly, our results did not confirm these expectations: q max and the SSA increased concomitantly with the increasing size of Fh-like Nps (Figure 6).…”
Section: Discussioncontrasting
confidence: 71%
“…The fraction of metal ions forming surface groups increases when the particle size decreases, leading to an increase in n H 2 O. Consequently, M nano increases when the particle size decreases, whereas ρ nano simultaneously decreases because the surface groups (−OH 2 and −OH) contribute more to the particle volume than to the mass. 36 …”
Section: Resultsmentioning
confidence: 99%
“… 23 , 25 , 32 In this approach, the nanocrystalline fraction of metal-(hydr)oxides is assessed using a traditional acid ammonium oxalate (AO) extraction 33 , 34 and next converted to the RSA (m 2 /g soil) using, for the extracted metal-(hydr)oxides, a standard value for the specific surface area (SSA) and a fixed value for the molar mass ( M nano ). However, this may lead to inconsistent results because both properties are particle size-dependent 35 , 36 and can greatly vary among soil samples. 37 39 …”
Section: Introductionmentioning
confidence: 99%
“…As an example, a small difference in the Fh-NP size such as 1.68 vs 1.65 nm would not lead to any modification of the Fh-NP EXAFS spectrum but can lead to a difference in the solubility product from Ks ~5.4 to Ks ~5.6 which leads to different Fh/oligomer ratios. 25,54 Accordingly, the observed slow decrease of the oligomer/Fh ratio after Fe(II) oxidation ( Figure 3a) can be explained by the ferrihydrite solubility decrease with its size growth over time.…”
Section: Resultsmentioning
confidence: 94%
“…Furthermore, it has been demonstrated that ferrihydrite particle size grows with ageing and pH increase, which leads to a decrease of the ferrihydrite solubility. 25,54 This phenomenon also contributes to the increase of the Fh/oligomer ratio over time. Figure 3a shows that, at the beginning of the reaction, Fh-NP and oligomers concentration grow concomitantly during Fe(II) oxidation, whatever the rate of Fe(II) oxidation.…”
Section: Resultsmentioning
confidence: 98%